Perfluorinated compounds: occurrence and risk profile - Kovarova, Jana; Svobodova, Zdenka (Neuro endocrinology letters, 2008)
Perfluorinated compounds (PFCs) such as perfluoro-octane sulphonate (PFOS) and perfluorooctanoic acid (PFOA) are emerging environmental pollutants, arising mainly from their use as surface treatment chemicals, polymerization aids and surfactants. They are ubiquitous, persistent and bioaccumulative in the environment. Perfluorinated compounds are being proposed as a new class of POPs. Although tests in rodents have demonstrated numerous negative effects of PFCs, it is unclear if exposure to perfluorinated compounds may affect human health. This review provides an overview of the recent toxicology and toxicokinetics, monitoring data now available for the environment, wildlife, and humans and attempts to explain the mechanisms of action of PFCs.
Keywords: Animals; ekosystém; Fluorocarbons; Fresh Water; Ecosystem; Humans; divoká zvířata; lidé; hodnocení rizik; zvířata; látky znečišťující životní prostředí; sladká voda; Animals, Wild; Environmental Pollutants; Risk Assessment; fluorokarbony